Archives management in Pasimasunggu Timur Sub-District Office, Selayar Islands Regency - Zulfitriani, Zulfitriani; Saleh, Sirajuddin; Nasrullah, Muh. (Jurnal Office, 2019)
the smooth running of offices. This study aims to determine the Management of Archives at the East Pasimasunggu District Office Selayar Islands Regency. This study used a qualitative descriptive approach with 5 informants. Data collection uses observation, interview and documentation techniques. While the data analysis technique used consists of four ways, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that archival management at the East Pasimasunggu District office of the Selayar Islands Regency is in a fairly good category. This is demonstrated through the focus of research, namely: the creation of the archive is in the good enough category, the use of the archive is in the good enough category, the storage of the archive is in the good enough category, the maintenance of the archive is in the not good category, the shrinkage and destruction is in the not good category.